Individual factors influencing contractors’ risk attitudes among Malaysian construction industries: the moderating role of government policy - D. M., Taofeeq; A. Q., Adeleke; Lee, Chia Kuang (Taylor & Francis, 2022)
This study investigated the individual factors affecting contractors’ risk attitudes and further determined its relationship with government policy. The theory of planned behaviour was used to develop the theoretical framework that investigated G-7 contractors operating in Malaysian construction industry. A review of relevant literature and questionnaire was adopted in order to identify the factors affecting contractors’ risk attitudes (individual factors). A total of 119 personal structured questionnaires were considered for the analysis with the response rate of 94%. In addition, a structural equation modelling approach was employed to examine the direct and the moderating relationship as drawn by the hypotheses. In addition, with quantitative research design following positivist research paradigm, the methodology was designed to focus on the research questions and the objectives. The questionnaire was designed by using closed interval measurement scale with proper care taken in designing the survey instruments. SPSS 20.0 and SmartPLS 3 for structural equation modelling were utilized in confirming the hypotheses developed for the study. The results of this study through structural equation modelling opined that government policy and individual factor have a positive and significant influence on contractor’s risk attitudes.